Pemberdayaan Petani Desa Dilem Gondang Melalui Pelatihan Pembuatan Kompos Padat Berbasis Kotoran Ternak dengan Pendekatan Manajamen Sumber Daya Lokal - Fajar Budiyanto; Kesia Dyar Prasetyawati; Fajarul Ihfan Nurhuda; Nopi Yanto; Riska Ayu Maharani; Alfi dwi Ixvi Anda; Ami Widyastutik; Selga Andry Virada; Ikhwan Zakariya; Deny Masyhuudulhaq; Khabib Ghofir Aszy Tullah; Hetri Alfiana Putri; Lu’lu’is Maulana Robby; Putri Dwi Lestari; Melisa Dian Pratiwi; Alfilreno Keysha Bima Muhammad; Fty Nadia Anabilah Mery Anggrek Ini; Imam Syafii; Muhamad Bahtiar Imaduddin; Zakva Wulidal Haqiqi; Mohammad Habibullah; Jati Nurul Ajizah; Regita Anjeli Putri Cayani; Rizki Edi Prahara; Selvi Kurnia Gusti (Lembaga Pengembangan Kinerja Dosen, 2026)
The farmer empowerment program in Dilem Village, Gondang District, was implemented through training on the production of solid compost based on livestock manure as an effort to enhance the independence and agricultural productivity of the local farming community. This training was designed to utilize local resources through a village potential–based approach that emphasizes the optimization of livestock waste and organic materials available in the surrounding environment. The implementation methods included socialization activities, material delivery, hands-on practice in compost production, and post-training assistance to ensure the sustainability of technology application at the farmer level. The results of the program indicated an increase in farmers’ knowledge and skills in the compost-making process, enabling them to produce organic fertilizer independently and reduce dependence on chemical fertilizers. This program also had a positive impact on soil quality, production cost efficiency, environmental cleanliness, and supported environmentally friendly and sustainable agricultural practices. Thus, this training activity contributes to strengthening the local economy, improving farmers’ welfare, and developing a sustainable agricultural system based on local resources in Dilem Village in a continuous and practical manner.